Kinerja Simpang Tak Bersinyal pada Simpang Jalan Antang – Jalan Rajawali Kota Palangka Raya - Palawa Nusa Tarip, Pratama; Devia; Elvina, Ina (Universitas Veteran Bangun Nusantara, 2024)
At the intersection of Jalan Antang - Jalan Rajawali, Palangka Raya City, it is an unsignalized intersection with four arms. At the location of Jalan Antang - Jalan Rajawali, Palangka Raya city, it is an area or area that is quite frequently passed by office workers, especially students and various groups of society. In this intersection area there are quite a lot of shops and it is also close to the Palangka Raya 3 Public Middle School, this condition is one of the factors that might cause delays and queues when passing through this intersection. The aim of this research is to analyze the performance of unsignalized intersections, as well as providing solutions or handling suggestions to improve the performance of the unsignalized intersections on Jalan Antang - Jalan Rajawali. Data collection was carried out over 4 days, namely Tuesday 4 June 2024, Wednesday 5 June 2024, Thursday 6 June 2024, and Monday 10 June 2024. The data collected was intersection geometry data and traffic volume data. The data analysis method uses the 2023 Indonesian Road Capacity Guidelines. The research results show that the highest peak hour traffic volume at the Jalan Antang - Jalan Rajawali intersection occurred on Tuesday, June 4 2024, in the morning period at 06.30-07.30 WIT with a traffic volume of 2874.6 pcu/hour. Where the capacity value (C) of the intersection is 3332 pcu/hour, the degree of saturation (DJ) is 0.862, the intersection delay is 14.748 seconds/pcu, and the queuing opportunity (Pa) is 29.845 – 58.956%. The intersection delay (T) of 14,748 is in the range of 5.1 – 15 so it is included in the service level category B. Based on the calculation results of solutions or handling proposals, namely the widening of major and minor roads has a degree of saturation with a value of 0.837, this has met the limit value set by The 2023 Indonesian Road Capacity Guidelines are the DJ value not exceeding 0.85 and the intersection service level index is category B.